Health Behaviors and Pandemics - Jay E. Maddock; Anna Greer (New Prairie Press, 2020)
Human health behaviors are essential to reducing the spread and impact of pandemics. However, most behavioral scientists do not work in the area of pandemics given the infrequency of their occurrences. This editorial examines relevant health behavior theories, in particular the precaution adoption process model, and how these apply to the COVID-19 pandemic.